Critical Challenges in Cultural-Historical Activity Theory: the Urgency of Agency - Stetsenko A.P. (Культурно-историческая психология, 2020)
The article addresses the challenge of conceptualizing agency within a non-dichotomous, dialectical approach that gives full credit to the social roots of agency and does justice to it being an achievement of togetherness possible only in a communal world shared with others. Critical steps in this direction are undertaken by the Transformative Activist Stance (TAS) approach advanced by this article’s author and further developed and applied to various topics by scholars from many parts of the world. This approach is firmly rooted in cultural-historical activity theory yet also moves beyond it in overcoming some of its impasses. The core elements of TAS are discussed to reveal how they coalesce on the nexus of social practices of self- and world-making. Agency is the process that enacts this nexus of ongoing, ceaseless social-individual transformations whereby people simultaneously, in one process, co-create their world and themselves so that each individual person makes a difference and matters in the totality of social practices. Ethical-political entailments of TAS are discussed to combat the legacy of passivity and inequality still permeating psychology and neighboring fields.